GALERI ANIMASI DI BANJARBARU - Rizali, Muhammad; Nurfansyah, Nurfansyah (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
The development of animation is growing rapidly every year, the use of animation which currently covers all fields, ranging from the world of entertainment to the world of business. The purpose of designing this Animation Gallery is to further introduce animation to the public. Animation Gallery will be designed using analogy methods and themed Hi-Tech Architecture. Animation is analogous to an architectural design by borrowing the principle of movement in the animation itself, namely how the stages of an object moving in an animation. Generally, movement in animation works with 2 elements, namely keyframe and in-between. If in architecture the keyframe is compared as a space and in-between as a circulation.